A novel biodegradable flowerpot prepared by fermented straw fiber and urea‐formaldehyde adhesive modified with keratin from waste feathers. Issue 4 (21st August 2021) - Du, Keke; Yong, Cheng; Guan, Mingjie; Xu, Xiangjun; Huang, Hongying; Sun, Enhui; Qu, Ping; Xu, Yueding
ABSTRACT: The recycling and utilization of feather waste from animal husbandry and straw from agriculture is a worldwide problem. In this study, keratin was extracted from waste feathers and used to modify urea‐formaldehyde (UF) adhesive to obtain biodegradable adhesive for making straw flowerpots with high performance. The results showed that keratin could reduce free formaldehyde and improve the thermal stability of UF. Furthermore, the mechanical properties of the flowerpot with keratin were greatly improved. The observed performance enhancements were attributed to the excellent adhesiveness of the bonding interface. In addition, the addition of keratin makes the flowerpot more hydrophilic and provides a better source of nutrients for microbes to grow and reproduce on the surface of the flowerpot, which is more conducive to the biodegradation of flowerpots after they are discarded. Our experiment suggests the great potential in terms of profitability and environmental protection by flowerpots prepared by fermented straw fiber and keratin‐modified UF. Abstract :